2014
DOI: 10.1155/2014/781863
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Sleep Deprivation and Continuous Exercise: Effects on Melatonin, Tympanic Temperature, and Cognitive Function

Abstract: The purpose of this study was to examine tympanic temperature, melatonin, and cognitive function during a 36-hour endurance event. Nine male and three female participants took part in a 36-hour sustained endurance event without sleep (N = 12, mean age = 31.8 ± 5.0 yrs). Participants were stopped for data collection at checkpoints throughout the 36-hour event. Tympanic temperature was assessed, a psychomotor vigilance test (PVT) was administered, and saliva samples were collected. Salivary melatonin was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…In fact, it is known that melatonin increases following long periods of exercise, especially if the body continuously works during the normal period of night time sleep, inducing altered circadian rhythms [ 57 ]. Several authors observed that either cognitive function or core temperature and melatonin production are altered during sleep deprivation in tandem with prolonged exercise [ 58 , 59 , 60 ]. In line with these reports, other authors showed that sleep deprivation increases melatonin release [ 55 , 56 ] and that a direct proportionality between melatonin release and the duration of sleep deprivation exists; in fact, the longer sleep the deprivation, the greater the melatonin release and drop in body temperature [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is known that melatonin increases following long periods of exercise, especially if the body continuously works during the normal period of night time sleep, inducing altered circadian rhythms [ 57 ]. Several authors observed that either cognitive function or core temperature and melatonin production are altered during sleep deprivation in tandem with prolonged exercise [ 58 , 59 , 60 ]. In line with these reports, other authors showed that sleep deprivation increases melatonin release [ 55 , 56 ] and that a direct proportionality between melatonin release and the duration of sleep deprivation exists; in fact, the longer sleep the deprivation, the greater the melatonin release and drop in body temperature [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This response to sleep deprivation is likely a physiological defence mechanism that could induce humans to sleep in order to regain normal physiological function [ 58 ]. However, in turn, high concentrations of melatonin were shown to increment IL-1β levels in mice splenocytes [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, mechanisms of sleep deprivation or even sleep restriction are likely to deeply impact, possibly in a transient way, the cognitive and sensory features of a person (Fullagar et al, 2015). Such effects seem to be more dramatic when sleep deprivation is combined with a massive physical effort, as occurs in these events (Davis et al, 2014; Hurdiel et al, 2015), also carrying on serious symptoms, including visual hallucination, possibly impacting the safety of athletes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, various evidence for significant effects on physical (Vitiello et al, 2013) and cognitive functions (Tomporowski, 2002; Cona et al, 2015; Hurdiel et al, 2015; Tonacci et al, 2016) of ultra-trailers has already been observed, mainly caused by a mix of high altitude exposure (Yan, 2014), environmental conditions (Lefferts et al, 2016; Taylor et al, 2016)—including cold, heat and hypoxia—muscular fatigue, dehydration (Cian et al, 2000), and sleep deprivation (Davis et al, 2014; Fullagar et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy almost different kinds of exercises and physical activities both acute and chronic could modify plasma melatonin levels. Meanwhile, endogenous profile of melatonin has different responses such as increase, decrease [19], or even unaffected to exercises that time of the day, and lighting condition is the most effective item on the melatonin secretion cycle even in response to exercises. As an overall consensus, those exercises which have been done at night or in the dark whether of moderate or high intensity result in delay in melatonin secretion.…”
Section: Muscle Development Is Under the Effects Of Program Variablesmentioning
confidence: 99%